2011
DOI: 10.1093/nar/gkr723
|View full text |Cite
|
Sign up to set email alerts
|

Histone hypoacetylation is required to maintain late replication timing of constitutive heterochromatin

Abstract: The replication of the genome is a spatio-temporally highly organized process. Yet, its flexibility throughout development suggests that this process is not genetically regulated. However, the mechanisms and chromatin modifications controlling replication timing are still unclear. We made use of the prominent structure and defined heterochromatic landscape of pericentric regions as an example of late replicating constitutive heterochromatin. We manipulated the major chromatin markers of these regions, namely h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 47 publications
6
61
1
Order By: Relevance
“…Previous studies showed that histone hypoacetylation is associated with replication timing of chromatin (68). Therefore, we investigated whether histone H3 acetylation and survivin have any effect on the KSHV genome copy number.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies showed that histone hypoacetylation is associated with replication timing of chromatin (68). Therefore, we investigated whether histone H3 acetylation and survivin have any effect on the KSHV genome copy number.…”
Section: Resultsmentioning
confidence: 96%
“…Acetylation of multiple sites on H3 and H4 histones was previously shown to influence origin activity, and hypoacetylation of these histones is thought to be necessary to maintain late replication timing (Unnikrishnan et al 2010;Casas-Delucchi et al 2012). Furthermore, there is evidence that replication timing itself can influence histone acetylation levels, and thereby transcription and nucleosome structure (Zhang et al 2002;Lande-Diner et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 75% of KRP5 targets are in heterochromatin regions, suggesting that KRP5 may modulate chromatin organization. Many lines of evidence link chromatin structure and DNA replication: replication timing requires specific chromatin marks (Casas-Delucchi et al, 2012), and recently, the chromatin factor CAF-1 has been implicated not only in the control of meristem structure but also in the control of genome replication at several stages of development (Exner et al, 2006). Another example is that mutations in the genes encoding the two homologous H3K27 monomethyltransferases ATXR5 and ATXR6 lead to the rereplication of specific genomic portions.…”
Section: Discussionmentioning
confidence: 99%